Environmental commitment among students of a Business School - Mantilla Escobar , Liliana Hilda (2023)
Sustainable development is a topic of particular interest in different nations around the world. In 2015, the United Nations designed the 2030 Agenda with 17 goals, including the eradication of poverty, combating climate change, and fostering sustainable cities and communities, among others. Therefore, it is essential to promote integration among various social actors, as well as public and private spheres, in order to consolidate these objectives. In line with this purpose, various educational institutions have adopted strategies that promote environmental awareness and understanding of sustainability among students. It is of interest to delve into the impact that volunteering activities have on strengthening environmental commitment among higher education students, considering the implications of these actions at both personal and professional levels. For this purpose, a survey was conducted among a sample of 63 students from the School of Global Business Administration at Ricardo Palma University in Peru. The survey aimed to explore the students' engagement with environmental causes and their perceptions of volunteering activities. The results suggest that these students are committed to environmental causes primarily due to their previous experiences. However, it is necessary to strengthen the connections established during volunteering programs beyond their completion, in order to promote the sustainability of these actions over time.